Identification and characterization of novel ETV4 splice variants in prostate cancer - Irene Cosi; Annalisa Moccia; Chiara Pescucci; Uday Munagala; Salvatore Di Giorgio; Irene Sineo; Silvestro G. Conticello; Rosario Notaro; Maria De Angioletti (Scientific Reports, 2023)
Abstract ETV4, one of ETS proteins overexpressed in prostate cancer, promotes migration, invasion, and proliferation in prostate cells. This study identifies a series of previously unknown ETV4 alternatively spliced transcripts in human prostate cell lines. Their expression has been validated using several unbiased techniques, including Nanopore sequencing. Most of these transcripts originate from an in-frame exon skipping and, thus, are expected to be translated into ETV4 protein isoforms. Functional analysis of the most abundant among these isoforms shows that they still bear an activity, namely a reduced ability to promote proliferation and a residual ability to regulate the transcription of ETV4 target genes. Alternatively spliced genes are common in cancer cells: an analysis of the TCGA dataset confirms the abundance of these novel ETV4 transcripts in prostate tumors, in contrast to peritumoral tissues. Since none of their translated isoforms have acquired a higher oncogenic potential, such abundance is likely to reflect the tumor deranged splicing machinery. However, it is also possible that their interaction with the canonical variants may contribute to the biology and the clinics of prostate cancer. Further investigations are needed to elucidate the biological role of these ETV4 transcripts and of their putative isoforms.